Development of Construction Occupational Health Safety Teaching Module for Students of the Department of Civil Engineering and Planning Education, Universitas Negeri Yogyakarta - Wahyu Dwi Santoso; Dian Eksana Wibowo; Cakra Nagara; Khoiru Harjanti; Ying-Dong Liu (Jurnal Pendidikan Teknik Sipil, 2025)
Background: This research aims to: (1) develop a construction occupational health safety teaching module for students of the Department of Civil Engineering and Planning Education, Universitas Negeri Yogyakarta. (2 Assessing the feasibility of the learning media through assessments from material experts and media experts from the Department of Civil Engineering and Planning Education, Universitas Negeri Yogyakarta. Methods: The research method employed is Research and Development, utilizing a 4D (Four-D) development model. This model comprises four stages of development: Define, which represents the definition stage; Design, referring to the planning stage; Development, denoting the development stage; and Disseminate, which leads to the dissemination stage. Data collection uses questionnaires, and the analysis method applied is descriptive techniques. Results: The results of the development of the K3 Construction module are (1) The development process follows 4 stages, namely define, design, develop, and disseminate. In the definition stage, it was found that there was a problem that learning media were not available for the construction occupational health safety teaching module for students of the Department of Civil Engineering and Planning Education UNY. At the design stage, the design of the module script is done with Microsoft Word with A4 paper size (21 cm x 29.7 cm). The development stage includes validation by material experts and media experts. (2) The results of validation from material experts resulted in a score of 90.66%, categorized as "very feasible", while validation from media experts received a percentage of 90.21%, also categorized as "very feasible". Conclusion: Media for the K3 Construction module that is suitable for use in the K3 Construction course, Department of Civil Engineering and Planning Education, Universitas Negeri Yogyakarta.